DYNAMIC SOCIAL EQUILIBRIUM IN WAKATOBI COASTAL COMMUNITIES: AN AGIL ANALYSIS OF POST-PANDEMIC TOURISM TRANSFORMATION - Soulthoni, Hannin Pradita Nur; Arsyad, Muhammad; Al Qhuraissy, Muammar Akbar (Universitas Padjadjaran, 2025)
Tourism growth in island regions has reshaped local livelihoods and social relations, raising questions about how communities maintain social balance amid economic change. This study examines how coastal communities in Wakatobi respond to tourism-driven transformation and maintain social equilibrium. Using a qualitative case study approach, data were collected through in-depth interviews with 18 informants, participant observation, and administrative data from 23 households. The analysis applies the AGIL framework to explore how economic, social, and cultural processes interact within the community. The findings show that tourism encourages livelihood diversification but also creates unequal access to opportunities. These pressures are managed through three key mechanisms: a shared orientation toward collective welfare, village deliberation as a form of social regulation, and the preservation of local cultural values as boundaries against market pressures. This study proposes the Island Social Equilibrium in Tourism Expansion (ISETE) model to explain how coastal communities respond to tourism-driven transformation. The findings demonstrate that social equilibrium is not a stable condition, but a continuously negotiated process shaped by tensions between economic change and social norms. The model offers a novel perspective by explaining how local communities actively sustain social stability rather than passively experiencing tourism impacts. These findings contribute to the understanding of social sustainability in tourism by highlighting the role of internal social system dynamics in maintaining community resilience.